2022
DOI: 10.1111/cns.14009
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation improves electroencephalogram functional connectivity of patients with minimally conscious state

Abstract: Aim: Deep brain stimulation (DBS) is a potential neuromodulatory therapy that enhances recovery from disorders of consciousness, especially minimally conscious state (MCS). This study measured the effects of DBS on the brain and explored the underlying mechanisms of DBS on MCS. Methods: Nine patients with MCS were recruited for this study. The neuromodulation effects of 100 Hz DBS were explored via cross-control experiments. Coma Recovery Scale-Revised (CRS-R) and EEG were recorded, and corresponding functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Several methods have been used to access functional connectivity after stimulation protocols. We can divide them into two categories: (a) non-invasive – which is transcranial magnetic stimulation (TMS), and (b) invasive: spinal cord stimulation (SCS) ( Bai et al, 2017 ), vagus nerve stimulation (VNS), and DBS ( Arnts et al, 2022 ; Dang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been used to access functional connectivity after stimulation protocols. We can divide them into two categories: (a) non-invasive – which is transcranial magnetic stimulation (TMS), and (b) invasive: spinal cord stimulation (SCS) ( Bai et al, 2017 ), vagus nerve stimulation (VNS), and DBS ( Arnts et al, 2022 ; Dang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, continuous stimulation will lead to fatigue and decreased nerve excitability of patients, so we adopted the strategy of intermittent stimulation. According to our previous experience that based on several spinal cord stimulation clinical studies, we believe that 15 min on and 15 min off is a very effective strategy 29…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous experience that based on several spinal cord stimulation clinical studies, we believe that 15 min on and 15 min off is a very effective strategy. 29 We also compared the CRS-R and GOS before and after the patients received DBS, and found that the behaviour and consciousness level of the patients have improved significantly. CRS-R is more detailed in the behavioural improvement among patients with DoC, while GOS is a more feasible score to assess whether the patient emerged from unconsciousness, and the effect of DBS in patients with DoC is consistent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations